PENGARUH PENGGUNAAN MEDIA FILM TERHADAP KETERAMPILAN MENULIS PUISI DI SD - Pratiwi, Santi Ayu; Halidjah, Siti; Asran, Mastar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this study is how the influence of the use of film media on the poetry writing skills of the fifth grade students on public elementary school 05 east Pontianak.This study aims to determine the effect of the use of film media on students poetry writing skills. This study uses an exsperimental method with a pre-exsperimental design of non equvalent control group design. The population is all students from five classes totaling 114 people, while the sample is class 5A and class 5B which amounts to 55 people. Data collection techniques are measurement techniques, with data collection tools are written essays. Based on data analysis, the result of the average post-test experimental class = 77,78 and average post-test result of the control class = 68,5. This shows an increase in students in learning to write poetry using film media. After ttest was obtained tcount 3,915 for dk 53 and Î±= 5% obtained ttable1,68355, which means tcount > ttable, then Ha is accepted, which means there is a significant influence on the use of film media. From the calculation of the effect size (ES), obtained (ES) of 1,02 with high criteria. Means the use of film media has a high influence on poetry writing skills.Key words : Influence,Â Film Media, Poetry Writing Skills.